2009
DOI: 10.1038/ncb1867
|View full text |Cite
|
Sign up to set email alerts
|

Telomere recombination requires the MUS81 endonuclease

Abstract: Telomerase-negative cancer cells maintain their telomeres via the Alternative Lengthening of Telomeres (ALT) pathway1–3. Although a growing body of evidence demonstrates that the ALT mechanism is a post-replicative telomere recombination process, molecular details of this pathway are largely unknown. Here we demonstrate that MUS81, a DNA structure–specific recombination endonuclease, plays a key role in the maintenance of telomeres in human ALT cells. We find that MUS81 specifically localizes to ALT-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 32 publications
6
98
0
Order By: Relevance
“…We find that TRF2 forms a complex with MUS81, inhibits the endonuclease activity of MUS81 by suppressing MUS81 binding to the DNA substrates, and mediates T-SCE through interaction with MUS81. 1 These findings, together with the fact that the MUS81 enzymatic activity is required for telomere recombination and ALT cell viability, support a model that TRF2 suppresses telomere recombination through regulation of the endonuclease activity of MUS81 in the ALT pathway (Fig. 2).…”
Section: Interaction Of Trf2 and Mus81 In The Alt Pathwaysupporting
confidence: 58%
See 3 more Smart Citations
“…We find that TRF2 forms a complex with MUS81, inhibits the endonuclease activity of MUS81 by suppressing MUS81 binding to the DNA substrates, and mediates T-SCE through interaction with MUS81. 1 These findings, together with the fact that the MUS81 enzymatic activity is required for telomere recombination and ALT cell viability, support a model that TRF2 suppresses telomere recombination through regulation of the endonuclease activity of MUS81 in the ALT pathway (Fig. 2).…”
Section: Interaction Of Trf2 and Mus81 In The Alt Pathwaysupporting
confidence: 58%
“…In our recent study, 1 we have demonstrated that the MUS81 endonuclease specifically localizes to APBs and associates with telomeric DNA in ALT cells, which is enriched during G 2 phase of the cell cycle ( Fig. 1).…”
Section: Activities Of Mus81 In Alt Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the functions of ERCC4(XPF) in processing of telomere structures via TERF2 (Zhu et al, 2003) may be coordinated by SLX4, which has independently been found at telomeres (Dejardin and Kingston, 2009). Likewise, SLX4 may facilitate MUS81-dependent recombination at telomeres (Zeng et al, 2009) Moreover, our data indicate that PLK1 can phosphorylate SLX4, suggesting a possible role for this kinase in conferring cell cycle control via SLX4 function. An understanding of the roles played by PLK1, as well as the novel SLX4-binding protein C20orf94, will require further study.…”
Section: Discussionmentioning
confidence: 87%